K teoriji prehoda med produkcijskimi načini - Kržan, Marko (Teorija in praksa, 2011)
The author attempts to define the criteria upon the basis of which we can talk of a transition between modes of production. Contrary to classical approaches that locate such criteria at the level of the forces of production and relations of exchange, the position adopted in this article is that of relations of production, defined as those social connections linking units of production. Following classical sociology, the author first distinguishes between organised and commodity forms of relations of production, then outlines the conditions under which the production of commodities becomes capitalist. These conditions are fulfilled whenever the commodity form of production encompasses the reproduction and allocation of the conditions of production. From this viewpoint the author then discusses whether it is pertinent to understand changes in the West and in China as a transition.
Keywords: Mode of production; Produkcijski način; Produkcijski odnosi; Production relations; Capitalism; Kapitalizem; Social change; Družbene spremembe